Seniors and their challenges - Leal, Arianne dos Santos; Nascimento, Oslei do; Rosa, Selma Almeida (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa, 2022)
The present work aims to analyze the care of the elderly, in having knowledge of the laws, public policies and the means to guarantee their rights. We cannot neglect or omit any kind of violence. Correct knowledge brings us benefits for a great quality of life. We can't just be concerned with one part of their lives, but with all areas. Research done through other articles, books show that we need to take a look at spiritual, social and psychological care that are very important areas for seniors. During the pandemic period, we realized the needs and challenges that the elderly had and still have. They were the most affected because they were part of the population most at risk of worsening Covid-19. The awareness of churches, families and the state in caring for the elderly is of paramount importance. Challenges continue both for the elderly and for those who take care of them, whether caregivers, family, church, society, etc.